Brutvögel auf ökologisch und konventionell bewirtschafteten Äckern in Norddeutschland - Neumann, Helge; Loges, Ralf; Taube, Friedhelm (2007)
A two-year comparative study on the abundance of breeding birds on conventional and organic arable fields was carried out in Northern Germany (federal state of Schleswig-Holstein). Birds were surveyed on 40 pairs of fields (conventional/organic), which were selected with regard to similar field sizes and comparable boundary struc-tures (hedges, shrubs). Averaged over two experimental years, skylarks (Alauda arvensis) as well as pheasants (Phasianus colchicus) occurred more often on organic fields, while yellow wagtails (Motacilla flava) reached higher abundances on conven-tional fields. Diversity of farmland birds was not affected by type of management. Concerning the regional threat of farmland bird species, organic farming might make a contribution to conserve and enhance the populations of skylarks.